Systematic Literature Review of Colonic Perforations in Vascular Ehlers-Danlos Syndrome - Walsh, Maura; Araradian, Cynthia Aline; Chen, Siting; Ali, Majdeddin Mohammed; Lian, Tiffany; Shalhub, Sherene; Fang, Sandy H. (Journal of Coloproctology, 2025)
Vascular Ehlers-Danlos Syndrome (VEDS) is a rare disorder caused by pathogenic variants in COL3A1 that cause a type III collagen abnormality or deficiency. Intestinal perforation is a known complication in this syndrome.The purpose of this meta-analysis is to quantify the risk of VEDS-associated intestinal perforation.A literature search was performed in August 2023 by PubMed, CINAHL, Cochrane, MEDLINE, and EMBASE identifying VEDS-related intestinal perforation publications. The search produced 615 articles with 530 articles screened. Two independent reviewers and a third reviewer for conflict resolution performed data extraction. Included studies discussed patients with VEDS and intestinal perforation. Reviews, case reports/series, expert opinions, consensus guidelines and abstracts only were excluded. Certainty of evidence was assessed by the Grading Recommendations, Assessment, Development and Evaluations framework. All data were reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Statistical R© software was used to calculate rates of colonic perforation and re-perforation.Four non-randomized studies were selected for the meta-analysis, which consisted of 721 patients with VEDS. The pooled colonic perforation rate was 15% (n = 111), and reperforation rate 33% (n = 29). Bowel perforation preceded the diagnosis of VEDS in 72% of patients. Considering the rarity of VEDS, limitations include lack of available data for patients. Given the small sample size, a large heterogeneity index was reported.While patients with VEDS have high colonic perforation and subsequent reperforation risks, many VEDS diagnoses are not made until after the inciting event. No consensus guidelines exist for the surgical management of VEDS-related bowel perforations.
Keywords: ehlers-danlos syndrome; type IV; intestinal perforation; colonic diseases